Analyzing Cause-and-effect Relationships among Key Determinats of Bank Customer Loyalty Using Fuzzy Cognitive Maps - Ferreira, F.; Ferreira, J.; Fernandes, C.; Meidute-Kavaliauskiene, I.; Jalali, M. (2015 BAI International Conference, 2015)
As a means of gradually increasing complementary margins and reducing the lack of liquidity caused by the most recent economic crisis, bank customer loyalty has been a fast growing concern for banking institutions. However, there is a widely recognized difficulty in identifying the factors that most contribute to creating and maintaining this loyalty. Based on the use of fuzzy cognitive mapping, we propose a framework that adds value to the way key determinants of bank customer loyalty are identified. This framework is the result of a process involving several bank branch front office employees, and follows a constructivist approach. Our findings suggest that the use of fuzzy cognitive maps (FCMs) allows the number of omitted determinants to be reduced and the understanding of the causal relationships between them to be improved. This not only increases transparency, but can also indicate what best practices should be followed to boost long-term relationships with bank customers. The strengths and limitations of our methodological framework are also analyzed.